The effects of the U.S. Plant Variety Protection Act on wheat genetic improvement - Alston, Julian M.; Venner, Raymond J. (International Food Policy Research Institute, 2000)
The U.S. Plant Variety Protection Act (PVPA) of 1970 was meant to strengthen intellectual property protection for plant breeders. A model of investment under partial excludability is developed, leading to the hypotheses that any increase in excludability or appropriability of the returns to invention, attributable to the PVPA, would lead to increases in investment or efficiency gains in varietal R&D, improved varietal quality, and enhanced royalties. These hypotheses are tested in an economic analysis of the effects of the PVPA on wheat genetic improvement. The PVPA appears to have contributed to increases in public expenditures on wheat variety improvement, but private-sector investment in wheat breeding does not appear to have increased. Moreover, econometric analyses indicate that the PVPA has not caused any increase in experimental or commercial wheat yields. However, the share of U.S. wheat acreage sown to private varieties has increased–from 3 percent in 1970 to 30 percent in the 1990s. These findings indicate that the PVPA has served primarily as a marketing tool with little impact on excludability or appropriability.